2011
DOI: 10.1007/s00167-011-1642-6
|View full text |Cite
|
Sign up to set email alerts
|

The influence of patellar position on soft tissue balance in minimal incision total knee arthroplasty

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 22 publications
2
16
0
Order By: Relevance
“…These effects could be attributed to the lateral shift and external rotation of the tibia with patella eversion [14]. This was also supported by prior studies demonstrating that patellar eversion increases the valgus alignment of the knee during soft tissue balancing with a tensor device [14,20]. These effects were greater in knee flexion, which is also supported by a previous study using intact cadaveric knees that showed that patella eversion decreases the flexion gap [18].…”
Section: Discussionsupporting
confidence: 70%
“…These effects could be attributed to the lateral shift and external rotation of the tibia with patella eversion [14]. This was also supported by prior studies demonstrating that patellar eversion increases the valgus alignment of the knee during soft tissue balancing with a tensor device [14,20]. These effects were greater in knee flexion, which is also supported by a previous study using intact cadaveric knees that showed that patella eversion decreases the flexion gap [18].…”
Section: Discussionsupporting
confidence: 70%
“…In order to permit soft tissue balancing under more physiological conditions during TKA, an offset type tensor was developed, with which soft tissue balance can be assessed throughout the range of motion under joint condition with reduced patellofemoral (PF), aligned tibiofemoral joints and femoral component in place [20, 25]. Using this tensor, we have reported intra‐operative soft tissue balance in CR and PS TKA [17, 19, 27, 32] and the relationship between intra‐operative soft tissue balance and flexion angles [19, 25, 40]. However, the influence of the tibial slope on intra‐operative soft tissue balance is unclear in both types of TKA.…”
Section: Introductionmentioning
confidence: 99%
“…Cadaveric studies by Luring et al have further confirmed that patellar eversion thus causes increased valgus during soft tissue balancing in TKA [32], which corresponds with our finding of reduced valgus/increased varus compared to native during both squatting and passive flexion obtained with the patella-in-place technique assessed in this study. Finally, trying to balance the tibiofemoral flexion gap with the patella in everted or subluxed position has been reported to influence tibial rotation in flexion and strain in the collateral ligaments [32,33,49], and thus likely played a role in our finding in terms of these specific biomechanical parameters.…”
Section: Discussionmentioning
confidence: 89%